Rituals of Banishment in Indonesia: Mysticism in the Film “Pengabdi Setan” - Nadia; Narrasyah; Kurniawati, Nia; Setiawati, Sulistia (Paradigma Lingua, 2025)
This study examines the narrative structure, characterization, and cultural significance of the Indonesian horror film Pengabdi Setan (2017), directed by Joko Anwar. By integrating modern horror filmmaking techniques with traditional mystical beliefs, particularly the concept of pesugihan (a supernatural means of acquiring fortune), the film reflects Indonesia’s ongoing negotiation between ancestral traditions and contemporary rationality. Through a qualitative analysis of plot structure and character arcs, this research highlights the film’s exploration of universal themes, such as familial sacrifice and the moral consequences of human choices. Furthermore, this study situates Pengabdi Setan within the broader context of Indonesian cinema’s cultural identity and its role in preserving and reinterpreting local myths. This analysis contributes to understanding how Indonesian horror cinema bridges local and global audiences, revitalizing the genre with culturally resonant narratives and global filmmaking techniques.